VOLATILITY MODELLING OF NIGERIA CONSUMER STAPLES STOCKS IN THE PERIOD OF GLOBAL ECONOMIC CRISIS (2012–2024) - Iro, Godwin Arunsi; Yahaya, Haruna Umar (FUDMA Journal of Sciences, 2025)
The period from 2012 to 2024 was faced with significant economic events and policy shifts in Nigeria, including fluctuations in oil prices, movements in consumer staple stocks, changes in government policies, currency devaluations, and the global impact of the COVID-19 pandemic. This study focuses on consumer staple stocks, specifically Nestle Nigeria Plc and Presco Plc which are the two leading consumer staple stocks listed on the Nigerian stock market. An empirical, quantitative time-series design using daily closing prices of these stocks of 2,809 observations per stock from 5th March 2012 to 11th June, 2024 were sourced and analysed. The analysis employs descriptive statistics, stationarity tests, and ARCH/GARCH family models to examine the return dynamics of Nestle Nigeria Plc and Presco Plc. The results reveal that Nestle Nigeria Plc had an average return of 0.000271 with a standard deviation of 0.020553, while Presco Plc recorded a higher average return of 0.001213 and exhibited greater volatility with a standard deviation of 0.027072. The Augmented Dickey-Fuller test confirmed that both stock return series were stationary at first differencing. The presence of significant ARCH effects in both series justified the application of GARCH-type models. Among the models evaluated, the Component GARCH (CGARCH) model provided the best fit for Nestle Nigeria Plc, while the Power ARCH (PARCH) model was most suitable for capturing the volatility of Presco Plc, based on the lowest AIC and SIC values. The study recommends further refinement of volatility models and the implementation of policy measures aimed at stabilizing stock price...